2013
DOI: 10.1186/1742-4933-10-21
|View full text |Cite
|
Sign up to set email alerts
|

Septic shock in older people: a prospective cohort study

Abstract: BackgroundSeptic shock is the first cause of death in Intensive Care Units. Despite experimental data showing increased inflammatory response of aged animals following infection, the current accepted hypothesis claims that aged patients are immunocompromised, when compared to young individuals.ResultsHere, we describe a prospective cohort study designed to analyze the immune profile of this population.ConclusionOlder people are as immunocompetent as the young individual, regarding the cytokines, chemokines and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 28 publications
(27 reference statements)
3
15
0
1
Order By: Relevance
“…Alternatively, the PSI score may less accurately reflect CAP severity in very old patients. Our results are supported by a study conducted in the ICU, reporting no differences in a large set of cytokines and chemokines between older and younger patients with septic shock at admission [21].…”
Section: Discussionsupporting
confidence: 87%
“…Alternatively, the PSI score may less accurately reflect CAP severity in very old patients. Our results are supported by a study conducted in the ICU, reporting no differences in a large set of cytokines and chemokines between older and younger patients with septic shock at admission [21].…”
Section: Discussionsupporting
confidence: 87%
“…Animal studies demonstrated that mortality, inflammation, hypothermia, apoptosis and disseminated intravascular coagulation are increased in aged animals subjected to experimental models of sepsis [ 21 ]. It is intriguing that despite the well characterized aspects of immunosenescence and the exaggerated inflammatory response detected in septic aged rodents [ 22 , 23 ], clinical studies conducted in humans (including those from our group) observed a similar immune profile when old and young septic critically ill patients were compared [ 24 – 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, 60% of all sepsis events and 80% of septic deaths occur in individuals over 65 years-old [26]. The incidence increases exponentially with age and older age is an independent risk factor for mortality among adults hospitalized with sepsis [26]. Elderly patients are particularly exposed to the risk of nosocomial infections [27].…”
Section: Discussionmentioning
confidence: 99%